Constructive alignment as a compensatory policy technology: A critical analysis of Vietnam’s revised foreign language proficiency framework - Hoa, Dinh Thi Phuong (Edelweiss Applied Science and Technology, 2026)
In contemporary education governance, competency frameworks have increasingly been employed as system-level regulatory devices, particularly in language education. When localized from international reference frameworks such as the CEFR, these frameworks are often accompanied by the expectation that Constructive Alignment can ensure the feasibility of reform through consistency between objectives, teaching, and assessment. This article aims to reconceptualize Constructive Alignment not as a purely pedagogical principle but as a compensatory policy technology mobilized to sustain reform under conditions of institutional capacity gaps. The analytical focus is placed on Vietnam’s Draft Seven-Level Foreign Language Proficiency Framework, examined in reference to the CEFR. The study employs critical policy analysis as a form of theoretical inquiry, drawing on a corpus of policy documents related to Vietnam’s foreign language proficiency framework and associated policy discourses. A three-layer model (normative – pedagogical – institutional), together with newly developed conceptual tools, is used to trace how alignment operates within the reform process. The findings indicate that, in the Vietnamese context, Constructive Alignment functions as a compensatory mechanism that enables the expansion of standards and CEFR integration while deferring corresponding institutional investment. Alignment, therefore, tends to stabilize reform rather than generate sustainable pedagogical transformation. The study contributes a new theoretical framework for analyzing alignment as a conditional policy technology, thereby extending international debates on CEFR localization, implementation capacity, and the politics of educational reform.